Redescription of Dysdera cylindrica (Aranei: Dysderidae) from Pakistan with notes on the distribution of the family - Marusik Yu.M. (K M K Scientific Press Ltd., 2022)
Dysdera cylindrica O. Pickard-Cambridge, 1885 is redescribed based on the lectotype male (designated here) and paralectotype female. The species was collected in northern Punjab, Pakistan, but not in Kashmir as indicated in the World Spider Catalog [2017]. Dysdera cylindrica together with D. arnoldii Charitonov, 1956 and D. subcylindrica Charitonov, 1956 form comprise the cylindrica species group. Dysderidae is a single family of spiders endemic to Palaearctic. The family ranges from Azores to Kyrgyzstan. Only six species, all from the genus Dysdera, are known outside the Palaearctic. Five of them are known exclusively from mountains adjacent to the Palaearctic. One species, D. crocata C.L. Koch, 1838 is cosmopolitan due to anthropogenic reasons.